Experimental Study on the Influence of Stress Concentration on the Flexural Stability of Aluminum Hollow Tube - Ganesh Radhakrishnan; Sami Sulaiman Al Khusaibi; Amjad Juma Al Subaihi; Al Azhar Zahir Al Ismaili; Al Salt Malik Al Maani (JMES: The International Journal of Mechanical Engineering and Sciences, 2023)
Solid sections are gradually replaced by the hollow sections in most of the structural applications in various engineering fields due to their attracting features such as light-weight and high specific strength. In the present investigation, one such attempt was made to investigate in detail about the flexural capability of an aluminum hollow tube (AHT) with square cross section. The objective of the investigation is to study about the influence of stress concentration on the flexural behavior of the hollow tube. The type of stress concentration considered in the investigation was through hole of different cross section and quantity. Three-point bending test with concentrated load is conducted on the specimens of hollow tube with different types of stress concentration such as circular hole, square hole and perforations. The load was applied manually during the bending test. The bending test was carried out on all specimens for various support span of 110, 130, 170 and 200 mm respectively. The output measures of the study are maximum bending load, deflection and flexural stiffness. The maximum bending load capacity around 5.7 kN was observed for AHT with circular hole with support span of 90 mm. The maximum deflection measured at the mid span of the beam increases rapidly when the aspect ratio increases from 73.33 to 93.33, whereas after which the variation of deflection is marginal for the increase in aspect ratio from 113.33 to 133.33. This was due to the effect of spring back, which dominates more on the bending behaviour at shorter span between the supports